Analisis Peran Hukum Perdata Internasional terhadap Penyelesaian Sengketa Paten Antara Apple dan Samsung - Yoel Adeputra; Muhaen Maya Wulandari; Dwi Imroatus Sholikah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The patent dispute between Apple Inc. and Samsung Electronics Co. Ltd. is one of the largest Intellectual Property Rights (IPR) conflicts in the modern technology industry. This case began in 2007, when Apple launched the first-generation iPhone, revolutionizing the smartphone market with its minimalist design, full-touch screen, and intuitive interface. The success of the iPhone opened new markets and positioned Apple as an innovation leader. Samsung, as the largest electronics manufacturer in Asia, then produced the Android-based Samsung Galaxy smartphone, which quickly became the iPhone's main competitor. This business competition then turned into a legal dispute when Apple considered Samsung's products too similar to its products. This case involves claims of infringement of design patents and utility patents filed in various jurisdictions such as the United States, South Korea, Japan, Germany, and the United Kingdom. This article uses a normative juridical method with a statutory and case approach. The analysis shows that the patent dispute between Apple and Samsung cannot be resolved through a single international forum due to the territorial nature of the patent system. Therefore, litigation takes place in several countries and results in varying decisions.